2019
DOI: 10.1159/000498984
|View full text |Cite
|
Sign up to set email alerts
|

Sex Influence on the Efficacy and Safety of Sacubitril/Valsartan

Abstract: Background: Women are underrepresented in sacubitril/valsartan (SV) clinical trials. The aim of this study was to assess sex-specific differences in efficacy, tolerability, and safety of SV in real-world heart failure with reduced ejection fraction (HFrEF) patients. Methods: A prospective registry in 10 centers including all patients who started SV during the last 6 months was analyzed in this study. Results: A total of 427 patients were included, 126 (29.5%) were women. There were no substantial differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
1
17
0
4
Order By: Relevance
“…These findings are in agreement with those of previous studies, which showed that sacubitril/valsartan therapy resulted in an equal inverse remodelling of the LV in women, diabetic individuals, and ischemic heart disease patients [ 37 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with those of previous studies, which showed that sacubitril/valsartan therapy resulted in an equal inverse remodelling of the LV in women, diabetic individuals, and ischemic heart disease patients [ 37 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…All cause-mortality was reported in five studies covering 684 subjects, with the incidence rate being 8 (95% CI 4-12)/100 person-year. 11,18,19,26,27 The hospitalization rate, as inferred by three studies with 390 patients in total, was 24 (95% CI 5-42)/100 person-year. 11,17,18 While there was no relationship between age or sex and all-cause mortality, male sex was negatively associated with hospitalization (weighted linear regression, β = À2.44, 95% CI À4.04 to À0.84; P = 0.03).…”
Section: Sacubitril-valsartan Management and Side Effects All-cause Mortality And All-cause Hospitalizationmentioning
confidence: 99%
“…Therefore, we could not adjust for patient-level characteristics. Fourth, all of our studies were completed in countries with predominant White populations (9,(13)(14)(15)(16). Consequently, our findings could not be extrapolated to other races.…”
Section: Limitationsmentioning
confidence: 95%